Complete Submodularity Characterization in the Comparative Independent Cascade Model - Chen, Wei; Zhang, Hanrui (In Proceedings of the 11th International Frontiers of Algorithmics Workshop (FAW'2017), Chengdu, China, June, 2017, 2017)
We study the propagation of comparative ideas in social network. A full characterization for submodularity in the comparative independent cascade (Com-IC) model of two-idea cascade is given, for competing ideas and complementary ideas respectively. We further introduce One-Shot model where agents show less patience toward ideas, and show that in One-Shot model, only the stronger idea spreads with submodularity.